Community assembly and inventory efficiency at a regional scale: the case of terrestrial Heteroptera (Insecta) in northern Patagonia, Argentina. Issue 6 (18th August 2018) - Diez, Fernando; Cornelis, Marcela; Pall, JosÉ Luis; CoscarÓn, MarÍa Del Carmen
Abstract : The first step to understanding the species present in a particular area is to perform inventory and assemblage studies. To obtain a species inventory, it is important to determine parameters such as species richness and relative abundance. This information can be useful for future studies and decision-making purposes in the conservation area. Despite the fundamental role of the terrestrial Heteroptera in ecosystems, they remain poorly known. We expected that the terrestrial Heteroptera species assemblage would be strongly associated with plant communities. Presently, 840 samples were collected in northern Argentine Patagonia during two years, 2013 and 2014. A total of 1950 adults of terrestrial Heteroptera belonging to 12 families, 32 species, and 8 morphospecies were found. Various statistical techniques were applied to correct the observed data for undersampling bias. These suggested that the lower boundary of the summer Heteroptera species richness in northern Patagonia was about 44–54 species. We concluded that the high regional habitat heterogeneity along the west-to-east and south-to-north gradients was paralleled by the turnover of Heteroptera. However, the Patagonian steppe shared a high number of species with the Monte and Subantarctic provinces. The suction sampling technique is an efficient technique to collect Heteroptera in environments with different plant structure and should thus be used in a complementary way with the sweeping technique.